Reflections on Self-awareness - Wesy, Lloyd W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This the prominent role that self-awareness now plays in popular psychology and in current speculations on counsellor education. Some lavish claims regarding the value of self-awareness are noted. Tlie content of self- awareness is considered and the various means by which it is achieved are described. The presumed relevance of self-awareness for counsellors is discussed and research related to that topic is briefly reviewed. In conclusion, a miscellany of counterviews is presented as an antidote to the potential excesses of prevailing opinion.